2001
DOI: 10.1159/000056138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diacerein on Indomethacin-Induced Gastric Ulceration

Abstract: We investigated the effect of diacerein, an antiosteoarthritic agent, and its metabolite, rhein, on the production of reactive oxygen species (ROS) from neutrophils as well as the protective effect of diacerein on indomethacin-induced gastric ulceration and its protection mechanism. Rhein inhibited the ROS production from N-formyl-methionyl-leucyl-phenylalanine or phorbol-12-myristate-13-acetate-activated human peripheral neutrophils. Indomethacin-induced gastric ulceration was significantly inhibited by oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…These finding were in agreement with [18] who postulated that, indomethacin's ability to cause cell damage may be related in part to its accumulation in these cells because of the phenomenon of ion trapping. Moreover, [19] suggested that, NSAIDs-induced impairment of the tight junction complex morphology and permeability between viable gastric mucosal epithelial cells may be a major contributing factor in the etiology of stomach disorder.…”
Section: Discussionsupporting
confidence: 92%
“…These finding were in agreement with [18] who postulated that, indomethacin's ability to cause cell damage may be related in part to its accumulation in these cells because of the phenomenon of ion trapping. Moreover, [19] suggested that, NSAIDs-induced impairment of the tight junction complex morphology and permeability between viable gastric mucosal epithelial cells may be a major contributing factor in the etiology of stomach disorder.…”
Section: Discussionsupporting
confidence: 92%
“…and Citrus aurantium L. Modern pharmacological research has demonstrated that WCST exerts a therapeutic effect by up‐regulating nitric oxide and acetylcholine (Li, Liu, & Liu, ), increasing the Ca 2+ level in gastrointestinal smooth muscle cells (Song et al, ) and increasing motilin, substance P and somatostatin in plasma (Guo, Liu, Wang, & Sun, ). In the early literature, related studies found that flavonoids (liquiritigenin, isoliquiritigenin and formononetin) and anthraquinones (emodin, rhein and aloe‐emodin) are the major effective constituents of corresponding individual herbs, and all of them have significant pharmacological activity, especially against Helicobacter pylori , gastric and duodenal ulcers, and spasmolysis (Goel, Das Gupta, Ram, & Pandey, ; Choi, Kim, Chae, & Chin, ; Chen et al, ; Wang & Chung, , Wang, Chung, Ho, Wu, & Chang, ; Chung et al, ; Tamura, Yokoyama, & Ohmori, ; Kakegawa, Matsumoto, & Satoh, ). Therefore, these six compounds are considered to be the main bioactive components of WCST based on their pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Rhein (4,5-dihydroxyanthraquinone-2-carboxylic acid) is a natural product derived from the rhizome of rhubarb which has been used medicinally in China for more than 1,000 years (7). Rhein possesses diverse biological properties such as antioxidant (8)(9)(10), anti-inflammatory (11,12), antiviral (13), antibacterial (14), antifungal (15), antiallergic (16) and anticancer (17)(18)(19)(20)(21)(22)(23)(24). The reported mechanism of the antitumor activity of rhein in cancer cells is due to its ability to induce apoptosis and/or cell cycle arrest in corresponding cancer cells (20,21).…”
Section: Introductionmentioning
confidence: 99%